(untitled) (Journal of Hama University, 2024)
The research aimed to study the value-added resulting from the manufacture of grape products (raisins, grape molasses, grape leaves, drinks...), this research in achieving its goal relied on a survey forms and interviews with producers who manufacture grape products in Salamieh district that were chosen in an Intended way, while respondents were selected in a random stratified way from the inhabitants of Salamieh city and surrounding villages whose inhabitants work in this industry by a number of manufacturers, Manufacturers whose production exceeds household consumption were targeted. The socio-economic characteristics of grape manufacturers have been studied and the costs of producing each product, the quantity of raw materials used and the manufacturing method, as well as the profit of each product and the value-added by manufacturing to the price of 1 kilogram of raw material have been identified. The results of the research showed that all manufactured products give value-added on the price of raw grape products but in varying proportions, as the greater value comes from grape leaves product and the manufacturing adds about (11751) SP on the price of 1 kg of raw leafs which means (391.7%) which is an excellent proportion, followed by the beverage product which gives an value-added estimated by (1928) SP on the price of 1 kg of raw grape that means (192.8%) which is a very good proportion, followed by raisin product which adds about (2473) SP on the price of 1 kg of grapes that means 164.9%, which is a good proportion, because the manufacturing costs are simple as its manufacturing depends on the energy of the sun. The two lowest value-added products are juices and grape molasses. However, they give value-added on the price of 1 kg of raw grapes, the juices adds (60.9%), while the grape molasses adds (142.2%), which are good values.